(untitled) (Journal of Global Humanities and Social Sciences, 2023)
With the continuous progress and development of the aviation industry, fuel consumption and carbon emissions have become important challenges for airlines. Therefore, from the perspective of green aviation, it is of great significance to explore the fuel-saving path of flight tests to reduce the fuel consumption and environmental impact of aviation operations. This path mainly includes optimizing air traffic management, improving aircraft fuel efficiency, strengthening fuel-saving operation training, and improving aviation fuel management. Through these measures, airlines can realize more economical and environmentally friendly flight methods and contribute to the sustainable development of the industry.